Methodology for Assessing Contractors by the Level of Compliance with the Deadlines for the Fulfillment of Contractual Obligations - T. G. Berezova (Статистика и экономика, 2025)
It is important to identify in advance, at the contracting stage, contractors who do not have sufficient economic resources to fulfill their obligations. This knowledge helps stakeholders to take additional measures to mitigate negative risks.Purpose of the study. To develop a methodology for monitoring and evaluation of contractors by the level of compliance with the terms of fulfillment of contractual obligations (including warranty obligations).Materials and methods. The information base of the study was the open data of the Unified Information System in the field of procurement, the State Information Resource of Accounting (Financial) Reporting. The following statistical methods were used in the study: descriptive statistics, discriminant analysis, probit regression, construction of integral indexes, typological grouping. The methodology is presented in the form of an algorithm containing the following stages of research: formation of initial data, identification of a specific indicator to be evaluated (term criterion), formation of a system of indexes to assess the level of compliance with the terms of fulfillment of contractual obligations (including warranty obligations), evaluation of the level of compliance with the terms of fulfillment of contractual obligations (including warranty obligations) (calculation of the integral index, typology of contractors, identification of new objects of observation by type of compliance with the terms of fulfillment of contractual obligations (including warranty obligations)) and development of recommendations to improve the level of compliance with the terms of fulfillment of contractual obligations.Results. The article classifies contractors participating in public procurement under 44 (Federal law) with the type of economic activity road construction on the basis of the introduced indicator term. The methodology of monitoring and evaluation of contractors by the level of compliance with the terms of fulfillment of contractual obligations (including warranty obligations) was proposed and tested on the real population. The integral index is calculated, which makes it possible to forecast the presumed facts of fulfillment of obligations on time and in violation of the term. A typology of contractors by the level of compliance with the terms of fulfillment of contractual obligations is carried out; a probit-regression equation is constructed taking into account industry specifics to identify new objects of observation by the type of compliance with the terms of fulfillment of contractual obligations. Conclusions and proposals for improving the level of compliance with the terms of fulfillment of contractual obligations at the considered economic entities are made.Conclusion. The considered methodology of statistical research allows monitoring and evaluation of contractors by the level of compliance with the terms of fulfillment of contractual obligations (including warranty obligations); to conduct inter-organizational comparisons both statically and dynamically; to determine the type of new objects of observation by the level of compliance with the terms of fulfillment of contractual obligations. The results of calculations can be used for benchmarking in terms of researching the organization’s own state, identifying industry leaders and competitors.